Keyword Programming for TouchDevelop - Gulwani, Sumit; Halleux, Jonathan "Peli" de (Proceedings of the 11th international conference on Mobile systems, applications, and services, 2013)
We designed and developed a new keyword programming environment in TouchDevelop: users simply type a set of keywords and the synthesizer generates snippets that most likely reflect the users' intent. Because the users can trigger the synthesis anywhere in their programs, the synthesizer also exploits program context to generate better snippets. The new environment bring benefits to both novice and experienced TouchDevelop users. Novice users can either use the tool to synthesize type-safe code from keywords, or to explore TouchDevelop features. Experienced users can use the tool to improve their productivity. The synthesizer was released and deployed together with TouchDevelop version 2.10.